2016
DOI: 10.1002/14651858.cd004541.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for treating depression in adults with end-stage kidney disease treated with dialysis

Abstract: Despite the high prevalence of depression in dialysis patients and the relative priority that patients place on effective treatments, evidence for antidepressant medication in the dialysis setting is sparse and data are generally inconclusive. The relative benefits and harms of antidepressant therapy in dialysis patients are poorly known and large randomised studies of antidepressants versus placebo are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 135 publications
0
57
0
Order By: Relevance
“…However, there is a paucity of conclusive evidence regarding the relative risks and benefits of antidepressants in patients with renal diseases. 18 On the other hand, nonpharmacological methods are more preferred than pharmacological methods for relieving depression and anxiety in hemodialysis patients due to lower side effects and costs, and limited potential for drug dependency. 16 Concerns about the side effects of medicines in hemodialysis patients have increased researchers' interests in the use of complementary and alternative medicine approaches.…”
Section: Relieving Anxiety and Depression In Hemodialysis Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is a paucity of conclusive evidence regarding the relative risks and benefits of antidepressants in patients with renal diseases. 18 On the other hand, nonpharmacological methods are more preferred than pharmacological methods for relieving depression and anxiety in hemodialysis patients due to lower side effects and costs, and limited potential for drug dependency. 16 Concerns about the side effects of medicines in hemodialysis patients have increased researchers' interests in the use of complementary and alternative medicine approaches.…”
Section: Relieving Anxiety and Depression In Hemodialysis Patientsmentioning
confidence: 99%
“…Current guidelines have recommended the use of a selective serotonin reuptake inhibitor for the treatment of depression in hemodialysis patients. However, there is a paucity of conclusive evidence regarding the relative risks and benefits of antidepressants in patients with renal diseases . On the other hand, nonpharmacological methods are more preferred than pharmacological methods for relieving depression and anxiety in hemodialysis patients due to lower side effects and costs, and limited potential for drug dependency .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are concerns as to whether their side effects can be well tolerated. 82 As medication count is high among patients with CKD/ESRD, adherence to pharmacological treatments may be more problematic in this population.…”
mentioning
confidence: 99%
“…In that study, it was observed that patients experienced changes in their life routines. Minor symptoms of anxiety and depression may affect the biopsychosocial dimensions [27]. This fact directly interferes with social coexistence and the possibility of autonomy, still possible in productive age.…”
Section: Discussionmentioning
confidence: 99%